2005
DOI: 10.1016/j.febslet.2005.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an actin‐binding site in p47phox an organizer protein of NADPH oxidase

Abstract: Actin has been reported to enhance the superoxidegenerating activity of neutrophil NADPH oxidase in a cell-free system and to interact with p47 phox , a regulatory subunit of the oxidase. In the present study, we searched for an actin-binding site in p47phox by far-western blotting and blot-binding assays using truncated forms of p47phox . The amino-acid sequence 319-337 was identified as an actin-binding site, and a synthetic peptide of this sequence bound to actin. The sequence shows no homology to other kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…In mammalian cells, the activity of NADPH oxidase is directly regulated by actin dynamics. Neutrophil NADPH oxidase binds to actin in vitro (Tamura et al, 2000a(Tamura et al, , 2000b(Tamura et al, , 2006. Actin polymerization activates NADPH oxidase, whereas depolymerizing actin deactivates it.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, the activity of NADPH oxidase is directly regulated by actin dynamics. Neutrophil NADPH oxidase binds to actin in vitro (Tamura et al, 2000a(Tamura et al, , 2000b(Tamura et al, , 2006. Actin polymerization activates NADPH oxidase, whereas depolymerizing actin deactivates it.…”
Section: Discussionmentioning
confidence: 99%
“…phox (32). In vascular smooth muscle cells, the angiotensin II-mediated activation of NADPH oxidase and ROS generation is regulated in part by p47 phox /actin interaction through cortactin; however, the mechanisms of this interaction remain unclear (33).…”
mentioning
confidence: 99%
“…For example, in a cell-free system, the addition of G-actin activated human neutrophil NADPH oxidase (31), whereas the addition of F-actin did not enhance oxidase activation. An actin binding site was identified in p47 phox (41). The present study showed that increased depolymerization of actin facilitated ROS production (Figs.…”
Section: Discussionmentioning
confidence: 68%